Monitoring aquaculture fisheries using Sentinel-2 images by identifying plastic fishery rings - Themistocleous, Kyriacos (My University, 2021)
Plastics in the marine environment constitute a significant problem globally. It is estimated that almost 8 million tonnes of plastic enter the oceanic ecosystem every year. A high concentration of plastics is found within the Mediterranean Sea, which is approximately 22,000 tonnes. Indeed, the South-East Mediterranean, where Cyprus is located, faces a significant problem with plastic debris. Aquaculture fisheries can contribute to marine debris, especially as a result of storm damage or accidents, as their plastic rings float in the ocean and end up in the coastline. Remote sensing techniques can be used to monitor fisheries and plastic debris in marine settings. More recently, research has focused on the ability to detect plastic litter in the water using remote sensing techniques. This paper examines how temporal series Sentinel-2 satellite images can be used to detect the plastic rings from aquaculture fisheries in the Vassiliko area in the south coast of Cyprus. This detection methodology can be used to manage and monitor fisheries using Sentinel-2 images.
Keywords: Remote sensing; Plastics; Fisheries; Satellite images; Sentinel-2; Spectral indices; Spectroscopy